Identification of salt stress-tolerant candidate genes in the BC2F2 population at the seedling stages of G. hirsutum and G. darwinii using NGS-based bulked segregant analysis - Shehzad, Muhammad; Ditta, Allah; Cai, Xiaoyan; Ur Rahman, Shafeeq; Xu, Yanchao; Wang, Kunbo; Zhou, Zhongli; Fang, Liu (Frontiers in Plant Science, 2023)
Salinity is the major threat to cotton seedlings, yield and productivity. In the present study we developed BC2F2 population of cotton plants from G. darwinii 5-7 and CCRI 12-4 salt susceptible parents to further identify salt-resistant candidate genes. The Illumina HiSeqTM strategy was used with Bulked Segregant Analysis. The salt resistant and salt susceptible DNA bulks were pooled by using 30 plants from BC2F2 population. Next Generation Sequencing was applied for the sequencing of parents and both bulks. Four significant genomic regions were determined, a first genomic region on chromosome 18(1.86Mb), a second and third genomic region on chromosome 25(1.06 Mb) (1.94 Mb) and the fourth on chromosome 08(1.41 Mb), respectively. The reads of Bulk01, Bulk02 were aligned to the G. darwinii and G. hirsutum genome, respectively, leading to the identification of 20,664,007 SNP/indel. After screening, 6573 polymorphic markers were obtained after filtration in candidate regions. The SNP-index in resistant and susceptible bulks and Δ (SNP-index) between resistant and susceptible bulks were measured. Based on the higher Δ (SNP-index) value, six effective polymorphic SNPs were selected in a different chromosome. Six effective SNPs were linked to five candidate genes in four genomic regions. Further validation of these five candidate genes was passed through the analysis RT-qPCR, expression profile that depicted two highly upregulated genes in salt tolerant species G. darwinii, Gohir.D05G367800 and Gohir.D12G239100, showed the reverse in G. hirsutum, except one gene, showed partial expression. The results indicated that Gohir.D05G367800, Gohir.D12G239100 is possible salt-tolerant genes. We are confident that the study may be helpful for the cloning, transformation and development of salt-resistance cotton varieties.